Clinical epidemiology and high genetic diversity amongst Cryptococcus spp. isolates infecting people living with HIV in Kinshasa, Democratic Republic of Congo - Bive, Bive Zono; Sacheli, Rosalie; Situakibanza Nani-Tuma, Hippolyte; Kabututu Zakayi, Pius; Ka, Alex; Mbula Mambimbi, Marcel; Muendele, Gaultier; Boreux, Raphael; Landu, Nicole; Nzanzu Mudogo, Celestin; M’Buze, Pierre-Robert; Moutschen, Michel; et al. (PLOS ONE, 2022)
Neuromeningeal cryptococcosis (NMC) is a life-threatening opportunistic infection in advanced HIV disease patients (AHDP). It is caused by Cryptococcus spp. complexes and mainly occurs in sub-Saharan Africa. In this study, we performed molecular characterization and antifungal susceptibility profiling of Cryptococcus isolates from AHDP in Kinshasa (DRC). Additionally, we investigated a possible association between NMC severity factors and the Cryptococcus neoformans (Cn) multilocus sequence typing (MLST) profiles. We characterized the isolates using PCR serotyping, MALDI-TOF MS, internal transcribed spacer (ITS) sequencing, and MLST. Susceptibility testing for the major antifungal drugs was performed according to the EUCAST guidelines. Parameters associated with NMC severity, such as hypoglycorrhachia (< 50 mg/dL), increased cerebral spinal fluid opening pressure (> 30 cm H2O), and poor therapeutic outcome were compared with the Cn MLST sequences type (ST). Twenty-three out of 29 Cryptococcus isolates were identified as serotype A using PCR serotyping (79.3%; 95% IC: 65.5–93.1), while six (20.7%; 95% IC: 6.9–34.5) were not serotypable. The 29 isolates were identified by ITS sequencing as follows: Cryptococcus neoformans (23/29, 79.3%), Cutaneotrichosporon curvatus (previously called Cryptococcus curvatus) (5/29, 17.2%), and Papiliotrema laurentii (Cryptococcus laurentii) (1/29, 3.5%). Using the ISHAM MLST scheme, all Cn isolates were identified as molecular type VNI. These comprised seven different STs: ST93 (n = 15), ST5 (n = 2), ST53 (n = 1), ST31 (n = 1), ST4 (n = 1), ST69 (n = 1), and one novel ST that has not yet been reported from other parts of the world and was subsequently assigned as ST659 (n = 2). Of the included strains, only Papiliotrema laurentii was resistant to amphoterin B (1/29, 3.5%), 6.8% (2/29) were resistant to 5-flucytosine (the single Papiliotrema laurentii strain and one Cryptococcus neoformans isolate), and 13.8% (4/29) to fluconazole, including two of five (40%) Cutaneotrichosporon curvatus and two of 23 (8.7%) C. neoformans strains. We found a significative association between poor therapeutic outcome and a non-ST93 sequence type of causative strains (these concerned the less common sequence types: ST53, ST31, ST5, ST4, ST659, and ST69) (87.5% versus 40%, p = 0.02). Molecular analysis of Cryptococcus spp. isolates showed a wide species diversity and genetic heterogenicity of Cn within the VNI molecular type. Furthermore, it is worrying that among included strains we found resistances to several of the commonly used antifungals.